Understanding the operatic tenor's legitimate head voice: A comparative study of historical and modern pedagogical approaches - Swan, Arthur (College of Music, 2022)
The modern operatic tenor, with his chest-voice-like upper register, produces a vastly different sound to that of the castrato-trained tenore di grazia of the eighteenth century. Notwithstanding this change in tenor vocality, the practice of register-blending or -unification, originally developed by the castrati as a means of extending their voices upwards with a seamless transition to the falsetto register, has remained a core element of classical voice training. The change in tenor vocality did, however, provide an impetus for the evolution of this pedagogical practice during the nineteenth century. It led to the emergence of “mixed voice” as the purported mechanism for the tenor's upper register, and the introduction of a more mechanistic approach to register-blending or -unification as a means of developing the mixed voice source mechanism. In light of more recent discoveries in voice science, the validity of the registerblending or -unification approach has been called into question. An important, albeit minority, view is that the tenor's legitimate head voice is simply an upwards extension of his chest voice mechanism. Science has not found any evidence of a “mixed voice” laryngeal mechanism, while there is evidence suggesting that it is possible to extend the chest voice mechanism upwards through vocal training that strengthens the thyroarytenoid muscle, coupled with the development of the necessary fine motor skill to maintain balanced adduction of the top and bottom edges of the vocal folds at high pitches. If this view is correct, it would have important implications for tenor training methods, in particular the practice of register-blending or -unification in the mechanistic sense.